Teknologi pemanfaatan limbah abu sekam padi menjadi paving blok - Yusuf, Andi Rumpang; Hijriah, Hijriah (Universitas Negeri Makassar, 2019)
Sidenreng Rappang districts is one of the rice producing centers in South Sulawesi. Along with the increasing amount of rice production, the waste produced by the production process also increases. Rice husk is a waste from the rice milling industry. Rice husk ash has very high pozzolanic activity so that it has the potential to be used as a substitute material or as a cement additive in a mixture of building materials such as paving blocks. Paving blocks are widely applied for road pavement, such as sidewalks, parking areas, residential streets, harbor areas, parks and others. Through the Community Partnership Program (PKM) efforts will be made to empower the community by involving farmer groups and youth youth groups in Kab. Sidrap in order to improve the economic life of the community. Communities are taught appropriate technology in making paving blocks through the use of press machines to produce paving made from raw rice husk ash which is expected to replace paving blocks from a mixture of cement and sand.